(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Starting from the last century and up to now, many studies were published in order to address the main causes of fraud. During their literary contributions, the researchers have introduced the auditing society with many theories about the fraud roots. The two most well-known theories was fraud triangle theory and the fraud diamond theory, and in the same context, This paper tried to figure out what might cause the fraud to be occurred. However, the concentration was on the causes that have not been tested yet. The empirical study is consist of two stages. The first one is the interview stage, which has been conducted with two types of participants (auditors and bank managers). This stage was aimed to highlight the main causes of fraud in the business environment of countries that were subject to the study (Jordan, Lebanon, and Syria). all auditors have focused on the factors of fraud triangle when they were talking about fraud causes. On the other hand, the bank managers participants provide different picture about fraud causes. they spoke about fraud triangle factors in addition to, another factor, they called it power or influence, and this factor seems to be unique to the developing countries environment. They explained this factor from many sides, and this explanation helped in formulating the 10 red flags of the new factor. The results of the interviews related to the power/influence factor have further tested using survey tool in the same countries. The respondents of this survey are practicing bank managers from banks in Jordan, Syria, and Lebanon. he participants were asked to indicate their opinion on the degree of importance of 10 red flags. the survey phase provides the statistical scale of each red flag, and it shows that the most important red flags were: 1- management failure to commit any investigation with suspect employees, 2- An employee in important position construct close relationships with parties in higher managerial level in the same company, 3- The ability of the person that construct close relationships with parties in higher managerial level to extend his relationships to low-level employees, to complete the fraud chain, 4- The company recruitment policy is subject to pressures from outside parties. based on the relative importance of the power/influence fraud risk factor’s indicators which was indicated by the participants in the survey and which hasn’t been studied before, this study added the fifth factor of fraud and under the name of power/influence to the other four risk factors identified previously in the previous studies.